(E)-6-Bromo-3-{2-[2-(2-chlorobenzylidene)hydrazinyl]thiazol-5-yl}-2H-chromen-2-one dimethyl sulfoxide monosolvate - Afsheen Arshad; Hasnah Osman; Chan Kit Lam; Madhukar Hemamalini; Hoong-Kun Fun (Acta Crystallographica Section E, 2011)
In the title compound C19H11N3O2SClBr·C2H6OS, the molecule adopts an E configuration about the central C=N double bond. The chromene ring system and the thiazole ring are approximately planar, with maximum deviations of 0.027 (2) and 0.003 (1) Å, respectively. The central thiazole ring makes dihedral angles of 21.82 (9) and 5.88 (7)° with the chloro-substituted phenyl ring and the chromene ring, respectively. In the crystal, molecules are connected via N—H...O, N—H...S and C—H...O hydrogen bonds, forming supramolecular chains along the c axis. An intramolecular C—H...O hydrogen bond occurs. π–π interactions are observed between the thiazole and phenyl rings [centroid–centroid distance = 3.6293 (10) Å]. A short Br...Cl contact of 3.37 (6) Å also occurs.